RESPONSE OF FREESIA (FREESIA REFRECTA L.) PLANT TO DIFFERENT GROWTH MEDIA, CALCIUM CHLORIDE AND GIBBERELLIC ACID - MOSA, HAJAR FAESAL; ABDULRAHMAN, YOUSIF ALI (Journal of Duhok University, 2022)
A pot experiment has been conducted in a plastic house at the Department of Protected Cultivation, Technical Institute of Zakho, Duhok Polytechnic University during the fall season of 2021–2022 to investigate the effects of three growth media (peat moss, loam + peat moss (1:1) and clay + peat moss (1:1)), foliar spraying of calcium chloride (CaCl2) at three concentrations (0, 500 and 1000 mg. L-1) and Gibberellic acid (GA3) at three concentrations (0, 200 and 400 mg. L-1) on vegetative growth, flowering and corm yield of freesia (Freesia refrecta L.) plant. The experiment was laid out in a Randomized Complete Block Design (RCBD) of three factors with three replicates. The obtained results displayed that the peat moss medium surpassed other media in giving the highest vegetative growth traits (plant height, leaf area, and number of leaves per plant) as well as enhancing flowering traits (number of florets/spike, and vase life of cut flower) and corm yield traits (number of produced corm/plant, and corm volume). The same significant impact was exhibited by CaCl2 at concentrations of 500 and 1000 mg. L-1. Whereas GA3 at concentrations of 200 and 400 mg. L-1 improved most studied traits except number of florets per plant and vase life of cut flowers. The maximum vegetative, flowering, and corm harvest traits were obtained from grown plants in peat moss medium and by spraying them with increased concentrations of CaCl2 and GA3. Therefore, the peat moss medium in combination with increased concentrations of GA3 and CaCl2 is recommended for the improvement of freesia production quality and vase life